2009
DOI: 10.1063/1.3267488
|View full text |Cite
|
Sign up to set email alerts
|

Lineshape analysis of Raman scattering from LO and SO phonons in III-V nanowires

Abstract: Micro-Raman spectroscopy is employed to study the phonon confinement in Au-and Mn-catalyzed GaAs and InAs nanowires. The phonon confinement model is used to fit the LO phonon peaks, which also takes into account the contribution to the asymmetry of the line shape due to the presence of surface optical ͑SO͒ phonons and structural defects. This also allows us to determine the correlation lengths in these wires, that is the average distance between defects and the defect density in these nanowires. Influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It has been showed that the shape (diameter 29 and cross section 30 ) of the nanowire, the surrounding medium, 31 and the defect density 32 of the nanowire influences the SO mode. Thus, the SO mode shifts to lower wave numbers when decreasing the diameter of the nanowire.…”
Section: Surface Optical Phonon In Inas Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been showed that the shape (diameter 29 and cross section 30 ) of the nanowire, the surrounding medium, 31 and the defect density 32 of the nanowire influences the SO mode. Thus, the SO mode shifts to lower wave numbers when decreasing the diameter of the nanowire.…”
Section: Surface Optical Phonon In Inas Nanowiresmentioning
confidence: 99%
“…5, a third mode at the lowenergy side of the LO mode can be observed and is assigned to the SO mode of InAs nanowires due to the localization in one dimension. 32,33 A polarized Raman study on this mode reveals that it only appears in parallel configuration x(y,y)x where the incident and scattered light polarizations are perpendicular to the wire axis [ Fig. 7(b)].…”
Section: Surface Optical Phonon In Inas Nanowiresmentioning
confidence: 99%
“…[22][23][24][25] Although the SO phonon has been investigated for thin films and for nanowires, there is no systematic study revealing the direct comparison between the actual defect density to the phonon propagation constant. Here, we exploit the dependence of the SO frequency on the propagation constant of the phonon to correlate the spatial period of the oscillation along the nanowire axis with the defect characteristics of the nanowires studied by TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Phonon confinement model (PCM) was applied to determine the correlation length of the LO phonon modes. 45 Raman intensity lineshape I(ω), is given by Eq. (6) using Gaussian confinement function for Wurtzite phases.…”
Section: Correlation Lengths Of Lo and So Raman Modesmentioning
confidence: 99%